Evolution of CGIAR funding - Beintema, Nienke M.; Echeverria, Ruben G. (International Food Policy Research Institute, 2020)
The primary role of international public agricultural research is undoubtedly to address key social, environmental, and economic goals at the global level. Further, there is consensus that investment must be accelerated in research-based innovations focusing on sustainable food systems. And given the relatively weak situation of many national agricultural research systems in the global South, it is imperative to reach economies of scale in investments in international initiatives. It is not yet clear, however, how much additional investment is needed or how scarce resources should be allocated across priority research-for-development challenges. At the international level, growing consensus indicates that—in addition to increasing funding—far greater harmonization is needed in funding and executing research in order to more effectively tackle global agricultural research challenges. Growing opportunities for technology spillovers and research alliances to occur across national, regional, and international boundaries necessitates the ability to access new technological knowledge from a variety of sources. And since access to new technologies is closely related to the capacity to generate new technologies, the need to strengthen and harmonize national, regional, and global research systems becomes even more of a priority. Although the role, contributions, and impacts of the CGIAR have been analyzed by many authors, only a few have summarized the recent evolution of its financing. This note is intended to contribute to reflections on the CGIAR’s first 50 years, which it will celebrate in 2021, while also providing a useful reference for the current “One CGIAR” governance and management transformation.